Circ_0043256 upregulates KLF2 expression by absorbing miR‐1206 to suppress the tumorigenesis of lung cancer - Ying Zhou; Hongliu Liu; Rui Wang; Mingtao Zhang (Thoracic Cancer, 2023)
Abstract Background Circular RNAs (circRNAs) have been reported to play roles in lung cancer development. The purpose of this work was to explore the function and mechanism of circ_0043256 in lung cancer tumorigenesis. Methods Quantitative real‐time polymerase chain reaction (qRT‐PCR) and western blot were used for the detection of the levels of genes and proteins. Cell growth, angiogenesis ability, migration, and invasion were analyzed by using 5‐ethynyl‐2′‐deoxyuridine (EdU) assay, flow cytometry, tube formation assay, transwell assay, and murine xenograft model, respectively. The target between miR‐1206 and circ_0043256 or Krüppel‐like factor 2 (KLF2) was verified by dual‐luciferase reporter assay. Results Circ_0043256 was a stable circRNA, which was found to be decreased in lung cancer tissues and cells. Functionally, forced expression of circ_0043256 suppressed lung cancer cell growth, angiopoiesis, migration, and invasion. Mechanistically, circ_0043256 directly bound to miR‐1206 and miR‐1206 targeted KLF2, circ_0043256 could regulate KLF2 expression via absorbing miR‐1206. Rescue assay showed that miR‐1206 overexpression reversed the anticancer effects of circ_0043256 on lung cancer cells. Moreover, inhibition of miR‐1206 could suppress the malignant phenotypes of lung cancer cells, which was attenuated by KLF2 knockdown. Pre‐clinically, lentivirus‐mediated circ_0043256 overexpression impeded lung cancer growth in nude mice. Conclusion Forced expression of circ_0043256 could impede the tumorigenesis of lung cancer via miR‐1206/KLF2 axis, indicating a potential therapeutic approach for lung cancer.